1963
DOI: 10.1139/m63-036
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Biosynthesis of Ergot Alkaloids

Abstract: DL-'l'ryptophan-P-C", but not L-phenylalanine-U-CL' nor ~-t v r o s i~l e -U -C~-~, is incorporated into the ergoline moiety of the ergot allialoids. The high specific activities of the bases isolated from cultt~res supplemented with a mixture of ~L -t r y~t o~h a n -P -C l~a n d carrier L-tryptophan indicate some contribution from the D-isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
2

Year Published

1965
1965
1978
1978

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 11 publications
2
4
0
2
Order By: Relevance
“…These results were expected in the light of other work (Groger et al, 1960;Taylor & Ramstad, 1960;Birch et al, 1960;Vining & Taber, 1963;Agurell, 1966;Majer et al, 1967;Castagnoli et al, 1970) the lysergic acid moiety of ergotamine is similar to that found for the other ergot alkaloids.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results were expected in the light of other work (Groger et al, 1960;Taylor & Ramstad, 1960;Birch et al, 1960;Vining & Taber, 1963;Agurell, 1966;Majer et al, 1967;Castagnoli et al, 1970) the lysergic acid moiety of ergotamine is similar to that found for the other ergot alkaloids.…”
Section: Discussionsupporting
confidence: 88%
“…Both L-[U-14C]phenylalanine and L-[U-14C]proline were found to be specific precursors for the constituent side-chain phenylalanine and proline moieties of ergotamine, confirming and extending the findings of Vining & Taber (1963) and Groger & Erge (1970). The fact that proline was not quite so specific a precursor as phenylalanine probably reflected the ease with which proline enters the tricarboxylic acid cycle through ready conversion into glutamate and ax-oxoglutarate; thus some random distribution of label supplied as proline may be expected.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Moreover, cardiovascular studies in the anesthetized intact dog and cat have demonstrated a significant blockade of the pressor response to exogenous epinephrine, with doses of cryogenine having no apparent effect on resting blood pressure (2,5).…”
Section: Sirmentioning
confidence: 99%